Modelagem hidrodinâmica em distintas áreas de intervenção de uso e ocupação antrópica no Cerrado Amazônico - (:unkn) unknown (Universidade Federal do Amazonas - Universidade do Estado do Amazonas, 2019)
Among many other ecosystems, the interaction analysis of water mechanics with biotic and abiotic components stands out the Amazonian Cerrado, which is surrounded by the Amazon Forest, creating a unique and dynamic mosaic of biomes and among these specificities in the region there is pressure exercised by man. Faced with this problem, this work has as its objective: to model the water flow, superficial and underground, in different areas of use and anthropic occupation on the natural Amazonian fields. With the method of overlapping topographic layers and dynamic fluctuation of surface and groundwater, associated to different types of use and occupation of areas of Amazonian savannas. This study found that the greater the disorganized interventions exerted by anthropic actions on a cerrado area, the greater the adverse consequences to the biotic and abiotic components of the environment, such as the increase of areas vulnerable to flooding and the emergence of temporary pools that can serve as breeding grounds vectors of disease transmission. However, such research may serve, for the managers of the society, subsidy of land management and planning under pressure of better drainage projects and, in general, basic sanitation projects for the southwest region of the Amazon.
Hydrodynamic modeling in different areas of intervention on use and anthropic occupation in the Amazon Cerrate
Keywords: Cerrados - Amazônia; Águas subterrâneas - Escoamento - Amazônia; ENGENHARIAS; Drenagem; Fluxo de água; Cerrado amazônico; Ações antropogênicas; Vulnerabilidade